From Filters to Scalpels—Understanding Perceptions of Facial Asymmetry: An AAFPRS Survey - Abraham-Aggarwal, Kiran; Chen, Xiaoxuan; Parsa, Keon M.; Frodel, John L. (Facial Plastic Surgery, 2024)
Facial asymmetries can significantly affect patient satisfaction post-surgery. Social media can impact a patient's perception of their asymmetries. To gather insights into the practices, perceptions, and approaches concerning facial asymmetry among facial plastic surgeons. The aim of this study was to understand the impact of social media on perceptions of facial asymmetry. This is an American Academy of Facial Plastic and Reconstructive Surgeons (AAFPRS) survey consisting of 46 questions that sought to understand facial plastic surgeons' perceptions of facial asymmetry, their consultation process, their patients' perspectives on their own facial asymmetries, and patient satisfaction. The survey was distributed to 1,269 members of AAFPRS across community hospitals, private practices, and academic hospitals. Sixty-seven members completed the survey. The survey revealed that 31% (21) of surgeons face challenges in managing patient expectations regarding facial asymmetry. In addition, 12% (8) of surgeons felt that patients did not initially recognize their own asymmetries. Eighty-seven percent (58) of surgeons emphasize the natural occurrence of asymmetry during consultations to set realistic expectations. This study emphasizes the need for thorough patient education during initial consultations to align expectations with achievable outcomes. Surgeons should explain the natural occurrence of asymmetry clearly and use digital imaging to show patients realistic previews of surgical results.
Keywords: facial asymmetry; facial plastic surgery; surgical outcomes; cosmetic enhancement; surgical planning; patient satisfaction